Correlación entre el Tiempo y Dimensión del Código en el Proceso de Desarrollo de Software en Concursos de Algoritmos. - Torres Guerrero, Francisco (Revista Daena: International Journal of Good Conscience, 2026)
Software projects require a major control in planning, management and development procedures. In the presentation are studied time relationship, code lines, functionality and difficulty. Source Line of Code a.k.a. SLOC is the tool used to evaluate the code dimension. A case study was made to gather data at TopCoder community, in which 24 software developers where evaluated in algorithms where 6 challenges were applied and each one had 3 difficulty levels. Results shown correlations between time and coded lines (R = 0.797), score and coded - lines(R = 0.757), time and difficulty (R = 0.537) which thrown positive values and means that variables have directly proportional relationships.